Trading spaces: How and why older adults disconnect from and switch between digital media. Issue 5 (20th October 2021) - Nguyen, Minh Hao; Hargittai, Eszter; Fuchs, Jaelle; Djukaric, Teodora; Hunsaker, Amanda
Abstract: Studies on disconnection from social media and related technologies tend to focus on the user's disconnection from one specific technology, and consequently provide an incomplete view. Drawing on in-depth interviews with 57 older adults ages 59+, we find that replacement is more common than complete disconnection, which suggests that research should consider people's larger digital media repertoire rather than focus on a single technology. Motivations for disconnection include social influences, lack of interest, convenience, time availability and overuse, privacy concerns, and technical barriers. We find that older adults' motivations for disconnection often mirror those of younger users reported in the literature, but some motivations are unique to older adults. Further, some disconnection motivations of younger users reported in the literature were not found in the responses of our sample of older adults. Overall, our study offers a nuanced view on experiences of ICT disconnection in the age of digital media ubiquity.